Paediatric pathology: a work in progress - Luiz Cesar Peres (University of São Paulo, 2014)
What is in fact the importance of Paediatric Pathology in developing countries? Why are there so few dedicated paediatric pathologists? The answers to these questions are not straightforward as there are probably many different reasons. What is perfectly understandable is the need for Paediatric Pathology to be practiced as a specialty and this can be demonstrated by some figures provided by the Instituto Brasileiro de Geografia e Estatística (IBGE).